Biogeochemistry of Cyclic Microelements in Hydromorphic Soils - Gulom Yuldashev; Inomjon Mamajonov (Zien Journals, 2023)
The work, based on its own and literary sources, presents materials on the content of iron, aluminium, silicon and other cyclic chemical elements in irrigated meadow saz soils with аrzyk-shokho metamorphic horizons of Central Fergana. It has been established that Fe, Al, Si and other cyclic elements accumulate at these horizons.
Keywords: cyclic elements; irrigated; grassland; lithosphere